Method for manufacturing electrodes for secondary batteries using non-aqueous electrolytes and binder for electrodes for secondary batteries using non-aqueous electrolytes
Patent Information
- Application Number
- JP2022103328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2022-06-28
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing electrode manufacturing methods using lithium containing fibrillated polytetrafluoroethylene (PTFE) face issues with high electrical resistance and uneven distribution of components, leading to decreased strength and flexibility.
A method involving a binder composition of polytetrafluoroethylene resin and conductive agents, prepared without a liquid medium, using a spray drying process to ensure uniform distribution and reduce resistance, characterized by a specific F/C ratio and fibril diameter.
The method results in electrodes with reduced electrical resistance and enhanced strength, suitable for lithium ion secondary batteries, improving battery performance and capacity.
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for manufacturing an electrode for a secondary battery using a non-aqueous electrolyte and a binder for an electrode of a secondary battery using a non-aqueous electrolyte.
Background Art
[0002] Using fibrillated polytetrafluoroethylene (PTFE) as a binder in an electrode of a lithium-ion battery containing a non-aqueous electrolyte has been considered (Patent Document 1).
[0003] Furthermore, obtaining a uniform mixed powder in which a conductive material is mixed with PTFE by spray drying has also been disclosed (Patent Documents 2 to 4).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Patent Document 3
Patent Document 4
Patent Document 5
Summary of the Invention
Problems to be Solved by the Invention
[0005] In the present disclosure, in an electrode using PTFE, a method for manufacturing an electrode for a secondary battery and a binder capable of reducing the electrical resistance value of the electrode and simultaneously making it excellent in strength can be provided. [Means for solving the problem]
[0006] This disclosure is, The composition consists of a polytetrafluoroethylene resin and a conductive additive, and contains an active material. A composition for electrode fabrication that substantially does not contain a liquid medium is made using a binder that is a powder and does not contain a liquid medium. A secondary battery electrode using a non-aqueous electrolyte, characterized by having a preparation step (1). This is the manufacturing method.
[0007] The above-mentioned binder preferably has a moisture content of 1000 ppm or less. The above binder is made by mixing a polytetrafluoroethylene resin and a conductive additive in the presence of a liquid medium. It is preferable that the product is manufactured by a manufacturing method that includes step (A) of causing the product to be produced. The above liquid medium is preferably water.
[0008] The above binder is used in the process of drying the composition obtained in step (A) by spray drying. It is preferable that the product is obtained by a manufacturing method having B). The above polytetrafluoroethylene resin preferably has a standard specific gravity of 2.11 to 2.20. It seems so. The above electrode manufacturing composition preferably contains a positive electrode active material.
[0009] The above-mentioned binder for secondary batteries is preferably a binder for lithium-ion secondary batteries. The above PTFE has a fibrous structure with a fibril diameter (median) of 150 nm or less. preferable. The above binder has an elemental ratio of fluorine to carbon (F / C ratio) of 0, as measured by elemental analysis. It is preferable that the value is between 0.4 and 3.0.
[0010] This disclosure relates to a composition comprising a polytetrafluoroethylene resin and a conductive additive, A secondary battery using a non-aqueous electrolyte characterized by being a powder that does not contain electrode active material. It is also an electrode binder.
[0011] The above-mentioned binder for secondary battery electrodes has an elemental ratio of fluorine to carbon measured by elemental analysis ( The F / C ratio is preferably 0.4 or more and 3.0 or less. This disclosure relates to polytetrafluoroethylene resin and Ketjenblack or carbon nano It is also a binder for secondary battery electrodes that uses a non-aqueous electrolyte containing a mixed powder with tubes. This disclosure is also characterized by containing the above-mentioned binder for secondary battery electrodes. This disclosure also relates to an electrode mixture characterized by containing the above-mentioned binder for secondary battery electrodes. . This disclosure also relates to an electrode characterized by having the above-mentioned electrode mixture. [Effects of the Invention]
[0012] In this disclosure, in electrodes using PTFE, the electrical resistance of the electrode is reduced, and simultaneously A method for manufacturing electrodes for secondary batteries and a binder that can also be made to have excellent strength. It can be provided. [Modes for carrying out the invention]
[0013] The details of this disclosure are described below. Electrode mixtures using PTFE as a binder sometimes resulted in high electrode resistance. The disclosure aims to resolve these problems and enable the acquisition of electrodes with low resistance values. The present invention provides a method for manufacturing electrodes.
[0014] Electrode mixtures that use PTFE as a binder are made by fibrillating the PTFE. This produces a binding agent effect. However, if electrodes are manufactured by mixing PTFE and a conductive additive as separate powders, The electrode may become highly resistive. This is because the PTFE is unevenly distributed within the electrode, affecting the conductivity. It is presumed that this is because the pathway is not sufficiently formed. Furthermore, a segregation of components occurs within the electrode. If this is the case, it can cause a decrease in electrode strength. On the other hand, if the mixture is kneaded vigorously to eliminate uneven distribution If this happens, excessive fibrillation of PTFE occurs, leading to a decrease in flexibility and strength. Therefore, use a binder that prevents uneven distribution of PTFE and conductive additives. And this can solve such problems.
[0015] A method for manufacturing electrodes for secondary batteries using a non-aqueous electrolyte disclosed herein is polytetrafluoroethylene The following are required: a fluororesin and a conductive additive, and a binder that is a powder and does not contain an active material. It is characterized by the following. Hereafter, this will be referred to as the first binder of this disclosure. The ingredients included in the adhesives and binders will be described in detail.
[0016] On the other hand, regarding the active material, if you try to mix PTFE and the conductive additive beforehand, it becomes a liquid. In the battery medium, moisture causes lithium to leach from the active material, leading to degradation of the active material and a decrease in battery capacity. It is known that this can lead to problems such as increased battery resistance (Patent Document 5). The binder used does not contain an active material and consists of a composition that requires PTFE and a conductive additive. By doing so, the objectives of this disclosure can be achieved without being limited by the active material.
[0017] Furthermore, polytetrafluoroethylene resin and Ketjenblack or carbon nanotubes Using a mixed powder with the obe as a binder is preferable because it can reduce electrode resistance. Such a binder can also achieve the objectives of this disclosure. The effect is not obtained when using other carbon-based conductive additives such as acetylene black. This is an effect that cannot be achieved. Such a binder will be referred to as the second binder of this disclosure.
[0018] A method for manufacturing a first secondary battery electrode using the non-aqueous electrolyte of the present disclosure comprises PTFE and conductive The binder is a powder consisting of a composition that requires auxiliary agents and does not contain an active material. It is characterized by the fact that the particles constituting the powder consist only of PTFE and conductive additives. It is not a single composition, but rather a composition containing both PTFE and a conductive additive.
[0019] The following provides a detailed description of such binders and the components they contain.
[0020] (Polytetrafluoroethylene resin) In this disclosure, the PTFE is not particularly limited and may be a homopolymer. It may be a copolymer that can be fibrillated, but homopolymers are more preferred. It's nice. In the case of copolymers, the fluorine atom-containing monomer that is the comonomer is chlorotrifluor. Fluoroethylene, hexafluoropropylene, fluoroalkylethylene, perfluoroethylene Examples include chloroethylene, fluoroalkyl fluorovinyl ethers, and the like.
[0021] The PTFE used as a raw material when preparing the electrode mixture according to this disclosure has a standard specific gravity of 2.11 to 2.20. It is preferable that the standard specific gravity is within that range, which allows for high-strength electricity It has the advantage of being able to produce electrode compound sheets. The lower limit of the standard specific gravity is 2.12 or less. It is preferable that the value is higher. The upper limit of the standard specific gravity is preferably 2.19 or less. Ideally, it should be 2.18 or less.
[0022] Standard specific gravity [SSG] was obtained by preparing the sample in accordance with ASTM D-4895-89. The specific gravity of the sample is measured by the water displacement method.
[0023] The PTFE used in this disclosure may have a core-shell structure. For example, PTFE can have a core of high molecular weight PTFE and a lower molecular weight PTFE in the particle. Examples include PTFE containing a shell of PTFE or modified PTFE. Examples of material E include PTFE, as described in Japanese Patent Publication No. 2005-527652. It is possible.
[0024] PTFE in powder form that satisfies the parameters described above can be obtained by conventional manufacturing methods. This is possible. For example, International Publication No. 2015-080291 and International Publication No. 2012-0 The manufacturing process should follow the instructions in publication number 86710, etc.
[0025] (Conductive additive) Any known conductive material can be used as the conductive additive mentioned above. A specific example is copper. , metal materials such as nickel, graphite such as natural graphite and artificial graphite, acetylene Rack, Ketchen Black, Channel Black, Furnace Black, Lamp Black Carbon black such as thermal black, needle coke, carbon nanotubes Carbon nanohorns, carbon nanofibers, fullerenes and graphene, VGC Examples include amorphous carbon materials such as F. In particular, Ketjenblack and acetylene black. Racks and carbon nanotubes are preferred. Among carbon nanotubes, multi-walled carbon Nanotubes are preferred. These may be used individually or in any combination of two or more types. They may be used in combination and in various ratios. Examples of commercially available carbon black include, for example, - Black #4300, #4400, #4500, #5500 etc (manufactured by Tokai Carbon Co., Ltd.) Furnace Black), Printex L, etc. (manufactured by Degussa, Furnace Black), Ra ven7000, 5750, 5250, 5000ULTRAIII, 5000ULTRA etc., Conductex SC ULTRA, Conductex 975ULTRA etc. , PUER BLACK 100, 115, 205 etc (made by Colombian, Furnace Bra #2350, #2400B, #2600B, #30050B, #3030B, # 3230B, #3350B, #3400B, #5400B, etc. (Mitsubishi Chemical Corporation, Furnace) Black), MONARCH1400, 1300, 900, VulcanXC-72R, BlackPearls2000, LITX-50, LITX-200, etc. (Cabot Corporation) Made in Furnace Black, Ensaco 250G, Ensaco 260G, Ensac o350G, Super-P Li (IMERYS, Furnace Black), Ketch Enblack ECP, ECP-600JD, Lionite CB, etc. (Lion Specialty) (Manufactured by I-Chemicals, Ketchenblack), Denka Black HS-100, Li-10 Examples include 0, FX-35 (manufactured by Denka Co., Ltd., acetylene black), etc. Commercially available VG Examples of carbon dioxide include VGCF-H (manufactured by Showa Denko Corporation). Commercially available multilayer carbon nanotubes Examples of tubes include the FT7000 (manufactured by CNano). Multilayer carbon nanotubes For the tube, the average outer diameter is preferably 4nm to 20nm, and 6nm to 12nm. More preferably, the average fiber length is 1 to 30 μm, and preferably 3 μm to 20 μm. It is preferable to do this. This will allow for good conductivity to be obtained. Even when manufacturing electrode sheets, if a conductive additive is added and mixed in before use That's fine.
[0026] The binder of this disclosure contains the above-mentioned conductive additive in a proportion of 1.0 to 60.0 by mass relative to the total amount of the binder. It is preferable to have this feature. This allows for good conductivity and electrode strength to be obtained. The above lower limit is more preferably 1.5 or higher, and even more preferably 2.0 or higher. The above upper limit is more preferably 55.0 or higher, and more preferably 50.0 or lower. It is preferable.
[0027] Furthermore, in this disclosure, it is essential that the binder contains a conductive additive, When manufacturing electrode sheets using electrode mixtures, additional PTFE and conductive additives are added. It is acceptable to use it in this way.
[0028] The above conductive additive is usually present in the electrode mixture at a concentration of 0.1% by mass or more, preferably 0.5% by mass or more. More preferably 0.8% by mass or more, and usually 50% by mass or less, preferably 30% by mass. It is preferable to use it in such a quantity of % or less, more preferably 15% by mass or less. Content If the content is lower than this range, conductivity may be insufficient. Conversely, if the content is higher than this range... If the battery level is too high, the battery capacity may decrease.
[0029] When mixing conductive additives with PTFE, materials added as needed include conductive materials and ions. Examples include powders and thickeners. For example, as a thickener, carboxymethylcellulose ( Celluloses such as CMC and methylcellulose (MC) can be suitably used.
[0030] When using these conductive additives and components other than PTFE, the amount of such components to be included is... Preferably, the proportion is 5.0% by mass or less relative to the total amount of binder. If the amount of this component exceeds 5.0% by mass, the objectives of the present invention may not be fully achieved.
[0031] (Binding agent) The binder used in this disclosure is a composition comprising PTFE and a conductive additive as essential components in powder form. This is the resulting shape. In other words, the composition is a mixture of PTFE and a conductive additive. It is in powder form, and the mixture of PTFE powder and conductive additive powder is included. No. This condition is not particularly limited, but granulation by spray drying It is particularly preferable that the particles are in a conditioned state.
[0032] The above binder contains PTFE and a conductive additive in a weight ratio of 99:1 to 50:50. It is preferable that the above mixing ratio is preferably 95:5 to 60:40. Preferably, the ratio is 90:10 to 65:35.
[0033] The method for manufacturing the above-mentioned binder is not particularly limited and can be manufactured by any method, however The manufacturing method also includes a step (A) of mixing PTFE and a conductive additive in the presence of a liquid medium. It is preferable that it is manufactured by [a specific method]. In this case, powder in a liquid dispersion of PTFE A method of adding and mixing a conductive additive, a liquid dispersion of PTFE and a liquid dispersion of the conductive additive. Methods such as mixing the body with other substances can be cited. Mixing can be done using general methods. For example, a disperser, homomixer, Examples include planetary mixers and other mixers, homogenizers, and wet jet mills. However, this is not limited to these.
[0034] In the above process (A), a dispersion containing PTFE, a conductive additive, and a liquid medium is used. The dispersion is such that the total amount of PTFE and conductive additive is PTFE, conductive additive and The amount is preferably 1 to 60% by weight of the total amount of liquid medium. The lower limit is 2 by weight. It is more preferable that it be % or more, and even more preferable that it be 3% by weight or more. The above upper limit is It is more preferably 50% by weight or less, and even more preferably 30% by weight or less. .
[0035] By mixing these in a liquid medium, PTFE and conductive additives can be mixed with high uniformity. This is preferable in terms of its properties. The liquid medium in such a mixture is preferably water.
[0036] In this case, the PTFE used as a raw material is an aqueous dispersion obtained by emulsion polymerization. It is preferable to do so.
[0037] The PTFE used as a raw material for the above-mentioned binder is an electric material that is stronger and has superior homogeneity. Since an electrode mixture sheet is obtained, it is preferable that the average primary particle diameter is 150 nm or larger. More preferably, it is 180 nm or more, and even more preferably 210 nm or more. Preferably, the wavelength is 220 nm or greater. The larger the average primary particle size of PTFE, the higher the extrusion pressure when using that powder for extrusion molding. The increase in force can be suppressed, and it also has excellent moldability. There is no particular upper limit, but 500 nm is Good. From the viewpoint of productivity in the polymerization process, the upper limit is preferably 350 nm.
[0038] The above average primary particle size was determined using an aqueous dispersion of PTFE obtained by polymerization, and the polymer concentration Transmittance of 550 nm projected light per unit length of an aqueous dispersion adjusted to 0.22 mass% This is compared with the average primary particle diameter determined by measuring the directional diameter in transmission electron microscope images. A quantity curve is created, the transmittance of the aqueous dispersion to be measured is measured, and the calibration curve is created. It can be determined based on this.
[0039] The mixture of PTFE and conductive additive mixed in the liquid medium by the above step (A) is then, It is preferable that the liquid medium is removed by drying by spray drying (step (B)). It seems so. Drying methods include, for example, shelf dryers, vacuum dryers, freeze dryers, hot air dryers, and drums. Examples include dryers and spray dryers. Spray drying is particularly preferred. Spray drying is a method of drying liquid This method involves spraying a mixture of a solid and a material into a gas and rapidly drying it to produce a dried powder. This makes it possible to obtain a binder in powder form in which PTFE and a conductive additive are uniformly mixed. Spray drying is a generally well-known method and can be performed using any known apparatus. This can be done using a general method. The above step (B) is a general method using a known general apparatus. This can be done by the following method. The drying temperature should be, for example, in the range of 100°C to 250°C. This is preferable. At temperatures above 100°C, the solvent can be sufficiently removed, and at temperatures below 250°C... This is preferable as it can further reduce energy consumption. A drying temperature of 110°C or higher is more preferable. A temperature of 220°C or lower is more preferable. The amount of supply liquid depends on the scale of production, but for example, The flow rate may be in the range of 0.1 L / h to 2 L / h. Also, the nozzle used to spray the prepared solution... The size depends on the scale of production, but for example, the diameter range is between 0.5 mm and 5 mm. That's good too.
[0040] The binder obtained in this way preferably has a moisture content of 1000 ppm or less. stomach. Because the moisture content is less than 1000 ppm, it exhibits low gas generation as an initial characteristic. It is preferable in that it can be used to manufacture rechargeable batteries. The above moisture content is more preferably 500 ppm or less.
[0041] [Measurement of moisture content] The moisture content of the binder is measured using a Karl Fischer moisture meter (AD) equipped with a boat-type moisture vaporizer. Using the P-511 / MKC-510N (manufactured by Kyoto Electronics Manufacturing Co., Ltd.), a moisture vaporizer was used for 21 The water vaporized by heating to 0°C was measured. Nitrogen gas was used as the carrier gas at a flow rate of 20°C. The mixture was flushed at 0 mL / min, and the measurement time was set to 30 min. Also, Karl Fischer reagent and ChemAqua was used. The sample volume was 1.5g.
[0042] The second binder of this disclosure is a polytetrafluoroethylene resin and Ketjenblack and It is a mixed powder with / or carbon nanotubes. Such a mixed powder contains a binder and When used in this way, acetylene braces can reduce electrode resistance and improve battery characteristics. This is preferable to using well-known carbon conductive additives such as buck, and the first method described above It can be used in the same way as a binder.
[0043] In the second binder described above, Ketjenblack and / or carbon nano The tube is not particularly limited and the above-mentioned ones can be used. Furthermore, carbon The nanotubes are preferably multilayered, and more specifically, have an average fiber length of 1 to It is preferable to use one that is 20 μm in size.
[0044] The polytetrafluoroethylene used in the second binder described above is the first binder described above. The same type of agent can be used.
[0045] The second binder described above is obtained through the same process (A) and (B) described above as the first binder described above. It may be something that can be produced, or it may be something obtained by simply mixing these components. stomach. In the electrode fabrication compositions described in detail below, both the first binder and the second binder are the same. It can be used in the following way.
[0046] (Composition for electrode fabrication) A composition for electrode fabrication refers to a composition that contains all the essential components for an electrode. That is, a state in which other electrode components such as electrode active material are mixed with the binder mentioned above. This refers to the composition. The electrode fabrication composition further includes, in addition to the above binder, an electrode active material, and This composition contains conductive additives and the like.
[0047] (electrode active material) The above positive electrode active material is one that is electrochemically capable of intercepting and releasing alkali metal ions. There are no particular restrictions as long as it contains an alkali metal and at least one transition metal. A substance is preferred. Specific examples include alkali metal-containing transition metal composite oxides, alkali metal -containing transition metal phosphate compounds, conductive polymers, and the like. Among them, as the positive electrode active material, in particular, an alkali metal-containing transition metal composite oxide that produces a high voltage is preferred. Examples of the above alkali metal ions include lithium ions, sodium ions , potassium ions, and the like. In a preferred embodiment, the alkali metal ion can be a lithium ion. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery. That is, in this embodiment, the alkali metal ion secondary battery is a lithium ion secondary battery.
[0048] Examples of the above alkali metal-containing transition metal composite oxide include, for example, Formula: M , c , , , 1-d , , , 2 , , 2 , , Mn 2-b M 1 b O4 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9 ≦ a; 0 ≦ b ≦ 1.5; M is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, C 1 r, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge) represented by an alkali metal-manganese spinel composite oxide, Formula: MNi[[ID=3 d O2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K) ;0≦d≦0.5;M 3 is Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti A small number of the following are selected from the group consisting of Mg, Ca, Sr, B, Ga, In, Si, and Ge. (both are a type of metal) Examples of alkali metal-cobalt composite oxides represented by are given above. In the above, M is preferably Or, one metal selected from the group consisting of Li, Na, and K, more preferably It is Li or Na, and more preferably Li.
[0049] In particular, MCoO2, which can provide a secondary battery with high energy density and high output, MMnO2, MNiO2, MMn2O4, MNi 0.8 Co 0.15 Al 0.05 O2, or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 is preferred and is represented by the following general formula (3). It is preferable that the compound is such that... MNi h Co i Mn j M 5 k O2(3) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K) M 5 is Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga It represents at least one selected from the group consisting of In, Si and Ge, (h+i+j+ k) = 1.0, 0 ≤ h ≤ 1.0, 0 ≤ i ≤ 1.0, 0 ≤ j ≤ 1.5, 0 ≤ k ≤ 0.2. .)
[0050] Examples of the alkali metal-containing transition metal phosphate compounds mentioned above include the following formula (4): M e M 4 f (PO4)g (4) (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K) M 4 A small amount is selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni, and Cu. At the very least, one compound is shown, and the compounds represented by (0.5 ≤ e ≤ 3, 1 ≤ f ≤ 2, 1 ≤ g ≤ 3) can be listed. In the above, M is preferably selected from the group consisting of Li, Na, and K. It is one type of metal, more preferably Li or Na, and even more preferably Li. ru.
[0051] Examples of transition metals in lithium-containing transition metal phosphate compounds include V, Ti, Cr, Mn, and Fe. Co, Ni, Cu, etc. are preferred, and specific examples include LiFePO4, Li3Fe Iron phosphates such as 2(PO4)3 and LiFeP2O7, and cobalt phosphates such as LiCoPO4 These lithium transition metal phosphate compounds consist of some of the transition metal atoms, such as Al and T. i, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Examples include those substituted with other elements such as silicon. The lithium-containing transition metal phosphate compound described above is preferably one having an olivine-type structure. stomach.
[0052] Other cathode active materials include MFePO4 and MNi 0.8 Co 0.2 O2, M 1.2 F e 0.4 Mn 0.4 O2, MNi 0.5 Mn 1.5 O2, MV3O6, M2MnO3 (formula Among them, M is at least one metal selected from the group consisting of Li, Na, and K.) etc. are mentioned. In particular, M2MnO3, MNi 0.5 Mn 1.5 Positive electrode active materials such as O2 are When the secondary battery is operated at a voltage exceeding 4.4V or a voltage of 4.6V or higher, the Crystal structure is preferably not collapsed. Therefore, an electrochemical device such as a secondary battery using a positive electrode material containing the positive electrode active material exemplified above Even when stored at high temperature, the residual capacity is less likely to decrease, The resistance increase rate is also less likely to change, and the battery performance does not deteriorate even when operated at a high voltage. Therefore , it is preferable.
[0053] As other positive electrode active materials, M2MnO3 and MM 6 O2 (where M is at least one metal selected from the group consisting of Li, Na, and K and M 6 is a transition metal such as Co, Ni, Mn, F e, etc.) and solid solution materials thereof are also mentioned.
[0054] As the solid solution material, for example, the general formula M x [Mn (1-y) M 7 y O z represented by is an alkali metal manganese oxide. Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K and M0.14 Ni 0.14 LiN is based on Li2MnO3, similar to O2. Manganese-containing solid solution materials containing iO2 or LiCoO2 have high energy density. This is preferable because it can provide an alkali metal ion secondary battery.
[0055] Furthermore, including lithium phosphate in the positive electrode active material is preferable because it improves continuous charging characteristics. There are no restrictions on the use of lithium phosphate, however, mixing the aforementioned positive electrode active material with lithium phosphate may be used. It is preferable to use it. The amount of lithium phosphate used is the same as the above positive electrode active material and lithium phosphate. With respect to the total, the lower limit is preferably 0.1% by mass or more, more preferably 0.3% by mass or more. More preferably 0.5% by mass or more, with an upper limit of preferably 10% by mass or less, more preferably The amount is 8% by mass or less, and more preferably 5% by mass or less.
[0056] The conductive polymers mentioned above include p-doped conductive polymers and n-doped conductive polymers. Examples of conductive polymers include polyacetylene-based and polyphenylene-based polymers. Examples include heterocyclic polymers, ionic polymers, ladder and network polymers, and the like. .
[0057] Furthermore, a positive electrode active material may be used in which a substance with a different composition is attached to its surface. i. Surface-adhering substances include aluminum oxide, silicon oxide, titanium oxide, and zirconium oxide. Magnesium oxide, calcium oxide, boron oxide, antimony oxide, bismuth oxide, etc. Oxides, lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate Sodium sulfates such as aluminum sulfate, lithium carbonate, calcium carbonate, magnesium carbonate Examples include carbonates such as um, and carbon.
[0058] These surface-adhering substances can be, for example, dissolved or suspended in a solvent and impregnated into the positive electrode active material, After addition, the method involves drying, or dissolving or suspending the surface-adhering substance precursor in a solvent to activate the positive electrode A method of impregnating or adding a substance and then reacting it by heating, etc., and adding to a positive electrode active material precursor. It can be attached to the surface of the positive electrode active material by methods such as adding and simultaneously firing it. When attaching a material, the carbonaceous material is mechanically attached afterwards, for example, in the form of activated carbon. Methods can also be used.
[0059] The amount of surface-adhering material is expressed in mass relative to the positive electrode active material, with a lower limit of preferably 0. The upper limit is 1 ppm or more, more preferably 1 ppm or more, even more preferably 10 ppm or more. Preferably, it is used in an amount of 20% or less, more preferably 10% or less, and even more preferably 5% or less. This is possible. The surface-adhering substance can suppress the oxidation reaction of the electrolyte on the surface of the positive electrode active material. This can improve battery life. However, if the amount applied is too small, the effect will not be sufficient. If it does not manifest, or if there is too much of it, it inhibits the movement of lithium ions, thus increasing resistance. There is a match.
[0060] The particle shape of the positive electrode active material is not limited to the conventionally used shapes such as clumps, polyhedrons, spheres, or ellipsoids. Examples include plate-like, needle-like, and columnar shapes. Furthermore, primary particles aggregate to form secondary particles. That's good too.
[0061] The tap density of the positive electrode active material is preferably 0.5 g / cm³ or more, more preferably 0.8 g / cm 3 More preferably 1.0 g / cm³ 3 That concludes the explanation. Tap density of the positive electrode active material If the above lower limit is not met, the required amount of conductive material and binder will increase during the formation of the positive electrode active material layer. The filling rate of the positive electrode active material into the positive electrode active material layer may be limited, which can restrict the battery capacity. By using composite oxide powder with high top density, a high-density positive electrode active material layer can be formed. This is possible. Generally, a higher tap density is preferable, and there is no particular upper limit, but if it is too high... The diffusion of lithium ions through the electrolyte within the positive electrode active material layer becomes the rate-limiting step, and the load Because the properties may be prone to degradation, the upper limit is preferably 4.0 g / cm³. 3 The following, Preferably 3.7 g / cm³ 3 More preferably, 3.5 g / cm³ 3 The following applies: In this disclosure, the tap density is defined as 5-10 g of positive electrode active material powder mixed with a 10 ml glass scalpel. The powder filling density (tapping) when the cylinder is filled and tapped 200 times with a stroke of approximately 20 mm. (Patent density) g / cm³ 3 We will seek it as follows.
[0062] Median diameter d50 of positive electrode active material particles (when primary particles aggregate to form secondary particles) The secondary particle size is preferably 0.3 μm or larger, more preferably 0.5 μm or larger, and even more preferably The particle size is preferably 0.8 μm or larger, most preferably 1.0 μm or larger, and also preferably 30 μm or less, more preferably 27 μm or less, even more preferably 25 μm or less, most preferably The size must be 22 μm or less. If the size falls below the above lower limit, it may not be possible to obtain a product with high tap density. If the upper limit is exceeded, the diffusion of lithium within the particles takes longer, leading to a decrease in battery performance. Problems such as the above may occur. Here, the positive electrode active material having different median diameters d50 By mixing two or more types, the packing properties during cathode fabrication can be further improved.
[0063] In this disclosure, the median diameter d50 is defined as a known laser diffraction / scattering particle size distribution analyzer. It is measured by the HORIBA LA-920 particle size analyzer. As the dispersion medium used during the process, a 0.1% by mass aqueous solution of sodium hexametaphosphate is used. After 5 minutes of ultrasonic dispersion, the measurement is performed with a set refractive index of 1.24.
[0064] When primary particles aggregate to form secondary particles, the average primary particle diameter of the positive electrode active material is Preferably, it is 0.05 μm or larger, more preferably 0.1 μm or larger, and even more preferably The particle size is 0.2 μm or larger, and the upper limit is preferably 5 μm or less, more preferably 4 μm or less. More preferably, it is 3 μm or less, and most preferably 2 μm or less. If it exceeds the above upper limit, it becomes spherical. It is difficult to form secondary particles, which negatively affects powder filling properties and significantly reduces the specific surface area. To achieve this, there is a higher possibility that battery performance, such as output characteristics, will deteriorate. Conversely, If the value falls below the lower limit, problems such as poor reversibility of charging and discharging usually occur because the crystal is underdeveloped. There are times when cheating is possible.
[0065] In this disclosure, the average primary particle diameter is measured by observation using a scanning electron microscope (SEM). It is determined. Specifically, in a photograph at 10,000x magnification, primary particles relative to a horizontal line. Find the longest intercept value between the left and right boundaries for any 50 primary particles, and then calculate the average value. It can be obtained by taking this.
[0066] The BET specific surface area of the positive electrode active material is preferably 0.1 m². 2 / g or more, more preferably 0.2 m 2 / g or more, more preferably 0.3m 2The value is 1 / g or more, and the upper limit is preferably 50m 2 / g or less, more comfortable 40 m 2 / g or less, more preferably 30m 2 B is less than / g If the ET specific surface area is smaller than this range, battery performance tends to decrease, and if it is larger, tap density decreases. This can sometimes lead to problems where the price becomes difficult to raise.
[0067] In this disclosure, the BET specific surface area is calculated using a surface area meter (for example, a fully automatic surface area meter manufactured by Okura Riken Co., Ltd.). Using a controlled apparatus, the sample was pre-dried at 150°C for 30 minutes under nitrogen flow, A nitrogen-helium mixture precisely adjusted so that the relative pressure of nitrogen to atmospheric pressure is 0.3. It is defined by a value measured using a gas and the nitrogen adsorption BET single-point method based on the gas flow method.
[0068] The secondary battery disclosed herein is a large lithium-ion secondary battery for hybrid vehicles and distributed power sources. When used in this context, high power output is required, so the particles of the positive electrode active material are mainly secondary particles. It is preferable that it be a body. The particles of the above positive electrode active material have an average particle diameter of 40 μm or less for secondary particles, and an average primary particle diameter of 40 μm or less. It is preferable that the mixture contains 0.5 to 7.0 volume percent of fine particles with a diameter of 1 μm or less. By including fine particles with a primary particle diameter of 1 μm or less, the contact area with the electrolyte is increased. This allows for faster diffusion of lithium ions between the electrode mixture and the electrolyte, As a result, the output performance of the battery can be improved.
[0069] For the production of the positive electrode active material, methods common to the production of inorganic compounds are used. Various methods can be considered to create spherical or ellipsoidal active materials, for example, transition Metal raw materials are dissolved or pulverized and dispersed in a solvent such as water, and the pH is adjusted while stirring. A spherical precursor is prepared and recovered, and after drying as needed, it is converted into LiOH, Li2CO3 Methods include adding a Li source such as LiNO3 and firing it at a high temperature to obtain an active material.
[0070] For the manufacture of the positive electrode, the positive electrode active material may be used alone, or two or more materials with different compositions may be used. They may be used in any combination or ratio. Preferred combinations in this case include: LiCoO2 and LiNi 0.33 Co 0.33 Mn 0.33 Combination with ternary systems such as O2 In addition, LiCoO2 and LiMn2O4, or a portion of the Mn in these, can be replaced with other transition metals, etc. A combination of these, or LiFePO4 and LiCoO2 or one of these Co Examples include combinations in which a portion is substituted with other transition metals, etc.
[0071] The content of the above-mentioned positive electrode active material is preferably 50-99.5% by mass in the positive electrode mixture for high battery capacity. More preferably, 80-99% by mass is preferred. Furthermore, the content of the positive electrode active material is preferably 80% by mass or more, more preferably 82% by mass or more. More preferably, it is 84% by mass or more. The upper limit is preferably 99% by mass or less. Preferably, it is 98% by mass or less. If the content of positive electrode active material in the positive electrode mixture layer is low, the electrical capacitance The quantity may be insufficient. Conversely, if the content is too high, the strength of the positive electrode may be insufficient. .
[0072] The negative electrode active material is not particularly limited and includes, for example, lithium metal, artificial graphite, graphite carbon fiber, Carbon produced by resin firing, carbon grown in the pyrolysis vapor phase, coke, mesocarbon microbeads (MCMB) ), furfuryl alcohol resin calcined carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon Fibers, natural graphite, carbonaceous materials such as non-graphitizable carbon, silicon, and silicon alloys. Silicon-containing compounds such as Li4Ti5O 12 Select one or more from the above. Examples of the above mixtures include those containing at least a portion of carbonaceous material. Alternatively, silicon-containing compounds can be used particularly favorably.
[0073] The negative electrode active material used in this disclosure preferably contains silicon as a constituent element. By including this element in the constituent elements, it is possible to create a high-capacity battery.
[0074] Silicon-containing materials include silicon particles and silicon nanoparticles dispersed in silicon-based compounds. Particles having a structure, silicon oxide particles represented by the general formula SiOx (0.5 ≤ x ≤ 1.6), and A mixture of these is preferred. Using these results in higher initial charge-discharge efficiency and high A negative electrode mixture for lithium-ion secondary batteries with high capacity and excellent cycle characteristics can be obtained.
[0075] In this disclosure, silicon oxide refers to amorphous silicon oxides, and silicon oxide before disproportionation. The element i is represented by the general formula SiOx (0.5 ≤ x ≤ 1.6). x is 0.8 ≤ x < 1.6. Preferably, 0.8 ≤ x < 1.3 is preferred. This silicon dioxide is, for example, silicon dioxide By heating a mixture of silicon and metallic silicon, silicon monoxide gas is produced, which is then cooled and precipitated to obtain silicon monoxide. It is possible.
[0076] Particles having a structure in which silicon nanoparticles are dispersed in a silicon-based compound include, for example, silicon fine particles. Methods of calcining a mixture of the material with a silicon-based compound, or disproportionation represented by the general formula SiOx The silicon dioxide particles are placed in an inert, non-oxidizing atmosphere such as argon at a temperature of 400°C or higher, preferably It can be obtained by heat treatment at a temperature of 800-1,100°C and carrying out a disproportionation reaction. The material obtained by the latter method is preferable because the silicon microcrystals are uniformly dispersed. Such disproportionation reactions can result in silicon nanoparticles with a size of 1 to 100 nm. Furthermore, regarding silicon dioxide in particles having a structure in which silicon nanoparticles are dispersed in silicon dioxide... In particular, silicon dioxide is desirable. Furthermore, silicon can be measured using a transmission electron microscope. It can be confirmed that nanoparticles (crystals) are dispersed in amorphous silicon dioxide.
[0077] The physical properties of silicon-containing particles can be appropriately selected depending on the desired composite particle. For example, The average particle size is preferably 0.1 to 50 μm, and more preferably 0.2 μm or larger at the lower limit. A thickness of 0.5 μm or more is even more preferable. The upper limit is more preferably 30 μm or less, and 20 μm or less is preferable. Furthermore, it is preferable. In this disclosure, the average particle size refers to the particle size distribution measurement by laser diffraction. This is expressed as the weight-average particle size in [location].
[0078] The BET specific surface area of silicon-containing particles is 0.5 to 100 m². 2 / g is preferred, 1 to 20m 2 / g is more preferable. BET specific surface area is 0.5m² 2 If the amount is greater than / g, the electrode is coated There is no risk of reduced adhesion and decreased battery performance. Also, 100m 2 / g or less If so, the proportion of silicon dioxide on the particle surface increases, making it suitable as a negative electrode material for lithium-ion secondary batteries. There is no risk of battery capacity decreasing when used in this manner.
[0079] By coating the silicon-containing particles mentioned above with carbon, conductivity is imparted, resulting in improved battery performance. As a method for imparting conductivity, a method of mixing with conductive particles such as graphite, the above Methods for coating the surface of silicon-containing particles with a carbon film, and methods combining both, etc. Examples include coating with a carbon film, and a preferred coating method is chemical vapor deposition (C The VD method is more preferable.
[0080] The amount of the above-mentioned negative electrode active material is set to 40% in the electrode mixture in order to increase the volume of the resulting electrode mixture. Preferably, it is % by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more. Yes. The upper limit is preferably 99% by mass or less, and more preferably 98% by mass or less.
[0081] (Other ingredients) The above electrode fabrication composition may further contain a thermoplastic resin. These include polyvinylidene fluoride, polypropylene, polyethylene, polystyrene, and polyethylene. Examples include terephthalate and polyethylene oxide. Even when using one type alone, or two types... The above may be used in any combination and ratio.
[0082] The ratio of thermoplastic resin to electrode active material is usually 0.01% by mass or more, preferably 0.0 It is 5% by mass or more, more preferably 0.10% by mass or more, and usually 3.0% by mass or less. Preferably, the amount is in the range of 2.5% by mass or less, more preferably 2.0% by mass or less. By adding a resin, the mechanical strength of the electrode can be improved. Also, within this range If it exceeds this, the proportion of electrode active material in the electrode mixture decreases, leading to problems such as a decrease in battery capacity. This can sometimes lead to a problem where the resistance between the active materials increases.
[0083] (Method of manufacturing electrodes) The electrode manufacturing method of this disclosure uses an electrode manufacturing composition obtained by mixing the above-mentioned components. It is preferable that this be formed into a sheet. In sheet formation, the drying process is omitted. Therefore, the amount of liquid medium used is reduced or eliminated entirely, and the powder is prepared without preparing a slurry. A preferred method involves applying shear stress to the electrode fabrication composition. Furthermore, a small amount of solvent may be added as a lubricant to reduce the load on the device. The solvent is an organic solvent. A solvent is preferable, and the amount of solvent contained is preferably 10% by mass or less relative to the electrode preparation composition. 5% by mass or less is more preferable, and 3% by mass or less is even more preferable. It is known that PTFE in powder form readily undergoes fibrillation when shear force is applied. By utilizing this fibrillating property, PTFE can be used as a binder. Yes, it is possible. In other words, the fibrillated PTFE becomes entangled with other powder components, The PTFE binds the powder components together, thereby acting as a binder when molding the powder components. It can act in this way.
[0084] Furthermore, even when using fibrillated PTFE as a binder, sufficient fibrillation is necessary. Otherwise, it will not be able to perform well when used as an electrode mixture. Furthermore, fibrils with a median fibril diameter (hereinafter simply referred to as "fibril diameter") of 20 nm or more By performing a fine fibrillation process that gives it a fibrous structure, fibrillation is achieved. PTFE can exhibit good performance as a binder for electrode mixtures.
[0085] The above electrode fabrication composition preferably contains substantially no liquid medium. Manufacturing of the present disclosure In the electrode obtained by this method, the fibrous structure has a fibril diameter (median) of 20 nm or more. It is preferable that the material has PTFE having a structure as a component. It is preferable that the fibril diameter (median) is 20 nm or more. That is, PTFE with a narrow fibril diameter is present in the electrode, and this causes the powder components that make up the electrode to interact with each other. It is desirable in that it provides both a binding effect and flexibility.
[0086] The above fibril diameter (median) was measured using the following method. (1) Using a scanning electron microscope (S-4800 model, manufactured by Hitachi, Ltd.), the electrode mixture sheet was examined. A magnified photograph (7000x) is taken to obtain the image. (2) Draw two lines horizontally at equal intervals on this image to divide the image into three equal parts. (3) For all PTFE fibers in the straight line above, 3 locations per PTFE fiber The diameter of each PTFE fiber is measured, and the average value is taken as the diameter of the PTFE fiber. The three measurement points are PT Select the intersection point of the FE fiber and the straight line, and locations shifted 0.5 μm above and below the intersection point. (Excluding unfiberized PTFE primary particles). (4) Perform the procedure in (3) above for all PTFE fibers that lie in the straight line below. (5) Starting from the first image, move 1 mm to the right of the screen and take another picture, and then proceed as described in (3) above and The diameter of the PTFE fiber is measured using (4). Repeat this process until the number of measured fibers reaches 80. The game ends when the number of books is exceeded. (6) The median of the diameters of all the PTFE fibers measured above was used as the fibril diameter.
[0087] The fibril diameter is preferably 15 nm or larger, and preferably 20 nm or larger. Ideally, the nanometer should be 31nm or larger. Excessive fibrillation leads to a loss of flexibility. This is a tendency. Also, there is no particular upper limit, but from the perspective of flexibility, for example, Preferably, it is 150nm or less, more preferably 100nm or less, and 75nm or less. Particularly preferable.
[0088] The method for obtaining PTFE having the above fibril diameter is not particularly limited, for example, (2) A step in which shear force is applied while mixing the above electrode manufacturing composition. Step (3) is to form the electrode mixture obtained in step (2) into a bulk form, and Step (4) involves rolling the bulk electrode mixture obtained in step (3) into a sheet. Therefore, we can list the methods for doing so.
[0089] Step (2) above involves mixing the electrode fabrication composition obtained in step (1) above while cutting. This is a step in which a breaking force is applied. Furthermore, powder components for preparing the electrode manufacturing composition are mixed. By applying shear force at the same time as mixing, the PTFE is fibrillated, and it can also be used as an electrode mixture. stomach.
[0090] In such a method, for example, in step (2), the mixing conditions of the electrode fabrication composition are By keeping the rotation speed below 2000 rpm, the fibrillation of PTFE is achieved while maintaining flexibility. This allows the process to progress, and by controlling the applied shear stress, the PTFE's properties can be improved. The brill diameter can be set to 20 nm or more.
[0091] Furthermore, after step (4), a larger load is applied to the resulting rolled sheet to make it even thinner. It is also preferable to have a step (5) in which the material is rolled into a sheet. That is also desirable. Furthermore, after step (4) or step (5), the obtained rolled sheet is roughly crushed and then subjected to further crushing. The fibril diameter can also be adjusted by having a step (6) of forming it into a U-shape and rolling it into a sheet. It can be adjusted. It is preferable to repeat step (6) for at least 1 to 12 times. .
[0092] In other words, by applying shear force, PTFE is fibrillated, and this becomes the electrode active material. By intertwining with powder components such as quality, an electrode mixture can be manufactured. The manufacturing method will be described later.
[0093] In the electrode manufacturing method of this disclosure, the PTFE content is the ratio of PTFE in the electrode mixture and And usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 1.0% by mass It is % or more, and usually 50% by mass or less, preferably 40% by mass or less, and more preferably The amount is 30% by mass or less, most preferably 10% by mass or less. If the proportion of the binder is too low, The inability to adequately hold the material results in insufficient mechanical strength of the electrodes, degrading battery performance such as cycle characteristics. This can sometimes lead to problems. On the other hand, if the temperature is too high, it can lead to a decrease in battery capacity and conductivity. be.
[0094] The electrode mixture of this disclosure can be used as an electrode mixture for secondary batteries. In particular, this disclosure The electrode mixture is suitable for lithium-ion secondary batteries. The electrode mixture disclosed herein is typically used in sheet form when used in secondary batteries. It can be done.
[0095] The following is an example of a specific manufacturing method for an electrode mixture sheet containing an electrode mixture. In the electrode manufacturing method disclosed herein, the electrode mixture sheet is (0) A step of preparing a mixture containing an electrode active material and, if necessary, a conductive additive. A step of preparing an electrode manufacturing composition containing a binder in the mixture obtained by step (0) above. (1) (2) A step in which shear force is applied while mixing the electrode fabrication composition. Step (3) is to form the electrode mixture obtained in step (2) into a bulk form, and Step (4) is to roll the bulk electrode mixture obtained in step (3) into a sheet. It can be obtained by a method for manufacturing electrode mixture sheets for secondary batteries having [the specified characteristic].
[0096] In step (2) above, when shear force is applied while mixing the electrode fabrication composition, The resulting electrode fabrication composition is simply a mixture of electrode active material, binder, etc. It exists in an intangible state. Specific mixing methods include W-type mixers, V-type mixers, and D Ram-type mixer, ribbon mixer, conical screw-type mixer, single-shaft kneader, twin-shaft kneader, mixer Methods of mixing include using a Kussmaller, agitator, or planetary mixer. ru.
[0097] In step (2) above, the mixing conditions can be set appropriately by adjusting the rotation speed and mixing time. For example, The rotational speed is preferably 2200 rpm or less. Preferably 10 rpm or more. More preferably 15 rpm or higher, and even more preferably 20 rpm or higher. Also preferably The engine speed is 2000 rpm or less, more preferably 1800 rpm or less, and even more preferably 1500 rpm. This is within the pm range. Below this range, mixing will take longer and will affect productivity. is given. Also, if it exceeds, fibrillation may progress excessively, resulting in an electrode with inferior strength and flexibility There is a risk of becoming a composite sheet.
[0098] In the above step (3), forming into a bulk shape means making the electrode manufacturing composition into one mass is what it is. Specific methods of forming into a bulk shape include extrusion molding, press molding, etc. Also, "bulk shape" is not particularly specified in terms of shape, as long as it is in a single mass state, and includes forms such as rod shape, sheet shape, spherical shape, cube shape, etc. The above mass Preferably, the diameter of its cross-section or the minimum side is 10,000 μm or more More preferably, it is 20,000 μm or more.
[0099] Specific rolling methods in the above step (4) include methods of rolling using a roll press, a flat plate press, a calender roll machine, etc. is mentioned.
[0100] Also, after step (4), it is preferable to have a step (5) of applying a larger load to the obtained rolled sheet and further rolling it into an even thinner sheet shape. It is also preferable to repeat step (5). In this way, instead of thinning the rolled sheet at once, by rolling it in stages little by little the flexibility becomes better. As the number of times of step (5), 2 or more and 10 or less is preferable, and 3 or more and 9 or less is more preferable Preferably. is more preferable. Specific rolling methods include, for example, rotating two or more rolls and passing the rolled sheet between them to process it into an even thinner sheet shape, etc. It is desirable to heat during rolling when rolling. The lower limit of the temperature range is preferably 40 degrees or more, and 50 degrees or more is more preferred Preferably, it is 60 degrees or higher. The upper limit is preferably 300 degrees or lower, and 250 degrees. A temperature below 200 degrees Celsius is more preferable, and a temperature below 200 degrees Celsius is even more preferable. Heating softens the sheet. It can be easily rolled.
[0101] Furthermore, in terms of adjusting the fibril diameter, after process (4) or process (5), the rolling sheet The process may also include a step (6) in which the material is roughly crushed, then reshaped into a bulk form, and rolled into a sheet. It is preferable. It is also preferable to repeat step (6). The number of times step (6) is performed is one or more. Preferably 12 times or less, and more preferably 2 to 11 times or less.
[0102] In step (6), a specific method for crushing the rolled sheet and forming it into a bulk form is to crush the sheet. Methods of folding a rolled sheet, or forming it into a rod or thin film sheet, chip Methods such as pulverization are mentioned. In this disclosure, "crushing" means making the material into a sheet in the next step. To roll it, the shape of the rolled sheet obtained in step (4) or step (5) is changed to another shape. It means to change something, and includes cases such as simply folding a rolled sheet. ru.
[0103] Alternatively, step (5) may be performed after step (6), and this process may be repeated. Furthermore, in steps (3) to (4), (5), and (6), uniaxial stretching or biaxial stretching is performed. You can go. Furthermore, the fibril diameter can be adjusted by the degree of coarse crushing in step (6).
[0104] In the above steps (4), (5), or (6), the rolling ratio is preferably 10% or more, more preferably The percentage is 20% or more, preferably 80% or less, more preferably 65% or less. More preferably, it is in the range of 50% or less. Below the above range, as the number of rolling cycles increases This will take more time and affect productivity. Also, if it exceeds this, fibrillation will be excessive. This can progress to the point where the electrode mixture sheet becomes inferior in strength and flexibility. The rolling ratio, as used here, refers to the percentage reduction in thickness after rolling compared to the thickness of the sample before rolling. Refers to. The sample before rolling may be a bulk electrode manufacturing composition, or a sheet-shaped electrode manufacturing composition. It may also be a composition. The thickness of the sample refers to the thickness in the direction in which the load is applied during rolling.
[0105] As mentioned above, PTFE powder fibrillates when shear force is applied. To obtain a fibrous structure with a fibril diameter of 20 nm or more, excessive shear stress is required. This can lead to excessive fibrillation, compromising flexibility. Also, it can result in weaker materials. The tensile stress may not be sufficient in terms of strength. Therefore, during mixing and rolling, it is necessary to apply an appropriate amount. Shear stress is applied to PTFE to promote fibrillation, and the resin is rolled and stretched into a sheet. By performing the above process within the specified range, fibrous material with a fibril diameter of 20 nm or more is produced. It may have a structure.
[0106] The electrode mixture sheet of this disclosure can be used as an electrode mixture sheet for secondary batteries. It can be either a negative electrode or a positive electrode. In particular, the electrode mixture sheet of this disclosure is lithium It is suitable for on-rechargeable batteries.
[0107] (positive electrode) In this disclosure, the positive electrode is composed of a current collector and an electrode mixture sheet containing the positive electrode active material. It is preferable that it be done. As the material of the current collector for the positive electrode, metals such as aluminum, titanium, tantalum, stainless steel, nickel, etc., or metal materials such as their alloys; carbon materials such as carbon cloth and carbon paper can be mentioned. Among them, metal materials, particularly aluminum or its alloy, are preferable. In the case of a metal material, examples of the shape of the current collector include a metal foil, a metal cylinder, a metal coil, a metal plate, expanded metal, punched metal, foamed metal, etc. In the case of a carbon material, examples include a carbon plate, a carbon thin film, a carbon cylinder, etc. Among these, a metal foil is preferable. The metal foil may be appropriately formed in a mesh shape. The thickness of the metal foil is arbitrary, but it is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handleability may be impaired.
[0108] In addition, it is also preferable from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode mixture sheet that a conductive aid is applied to the surface of the current collector. Examples of the conductive aid include carbon and noble metals such as gold, platinum, and silver. The ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet is not particularly limited, but the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution) / (the thickness of the current collector) is preferably 20 or less, more preferably 15 or less, most preferably 10 or less, and preferably 0.5 or more, more preferably 0.8 or more, and most preferably in the range of 1 or more. Exceeding this range
[0109]
[0110]
[0111]
[0112] [[ID=For the ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet, although it is not particularly limited, the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution) / (the thickness of the current collector) is preferably at most 20, more preferably at most 15, most preferably at most 10, and preferably at least 0.5, more preferably at least 0.8, and most preferably in the range of at least 1. Exceeding this range [[ID=For the ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet, although it is not particularly limited, the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution) / (the thickness of the current collector) is preferably at most 20, more preferably at most 15, most preferably at most 10, and preferably at least 0.5, more preferably at least [[ID=For the ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet, although it is not particularly limited, the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution) / (the thickness of the current collector) is preferably at most 20, more preferably at most 15, most preferably at most 10, and preferably at least 0.5, more preferably at least [[ID=For the ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet, although it is not particularly limited, the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution) / (the thickness of the current collector) is preferably at most 20, more preferably at most 15, most preferably at most 10, and preferably at least 0.5, more preferably at least [[ID=For the ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet, although it is not particularly limited, the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution) / (the thickness of the current collector) is preferably at most 20, more preferably at most 15, most preferably at most 10, and preferably at least 0.5, more preferably at least [[ID=For the ratio of the thickness of the current collector to the thickness of the positive electrode mixture sheet, although it is not particularly limited, the value of (the thickness of the positive electrode mixture sheet on one side immediately before injecting the electrolytic solution). Furthermore, during charging and discharging at high current densities, the current collector may generate heat due to Joule heating. If the value falls below a certain range, the volume ratio of the current collector to the positive electrode active material increases, and the battery capacity decreases. There is a match.
[0111] The positive electrode can be manufactured by conventional methods. For example, the electrode mixture sheet and the current collector can be bonded together with an adhesive. Methods include stacking the materials and then vacuum drying them.
[0112] The density of the positive electrode mixture sheet is preferably 3.00 g / cm³. 3 The above is more 3.10 g / cm 3 More preferably 3.20 g / cm³ 3 The above, and preferably 3. 80g / cm 3 The following, more preferably, is 3.75 g / cm³. 3 More preferably 3.70 g / cm 3 The range is as follows. If this range is exceeded, electrolysis occurs near the interface between the current collector and the active material. The permeability of the liquid decreases, and the charge / discharge characteristics, especially at high current densities, deteriorate, making it impossible to obtain high output. Yes, if the value falls below a certain level, the conductivity between the active materials decreases, increasing the battery resistance and preventing high output from being obtained. There is a match.
[0113] The area of the positive electrode compound sheet is determined from the perspective of improving stability at high power and high temperatures, and the battery casing case It is preferable to increase the outer surface area. Specifically, the surface area of the secondary battery casing It is preferable that the total area of the electrode mixture on the positive electrode is 15 times or more in area ratio, and furthermore 40 It is more preferable to make it more than double. The outer surface area of the battery casing refers to the case of a bottomed rectangular shape. This refers to the length, width, and thickness dimensions of the case portion containing the power generation element, excluding the protruding terminals. This refers to the total area calculated from the terminals. In the case of a bottomed cylindrical shape, it refers to the power generation area excluding the terminal protrusions. This is the geometric surface area of the case portion filled with the material, approximating it as a cylinder. (Positive electrode electrode mixture area) The sum of these is the geometric surface area of the positive electrode mixture layer facing the mixture layer containing the negative electrode active material, and the current collector In a structure in which a positive electrode mixture layer is formed on both sides via foil, the surface of each side is calculated separately. It refers to the sum of the products.
[0114] The thickness of the positive electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the current collector is subtracted. The thickness of the composite sheet is preferably 10 μm or more as a minimum for one side of the current collector. More preferably 20 μm or more, and preferably 500 μm or less as an upper limit. Preferably, the particle size is 450 μm or less.
[0115] Furthermore, a positive electrode with a different composition attached to its surface may also be used. Surface-adhering substances include aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, and acid Magnesium oxide, calcium oxide, boron oxide, antimony oxide, bismuth oxide, etc. Substances, lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate , sulfates such as aluminum sulfate, lithium carbonate, calcium carbonate, magnesium carbonate, etc. Examples include carbonates and carbon.
[0116] (Negative electrode) In this disclosure, the negative electrode is composed of a current collector and an electrode mixture sheet containing the negative electrode active material. It is preferable that it be done. The material used for the negative electrode current collector can be a metal such as copper, nickel, titanium, tantalum, or stainless steel. Examples include metallic materials such as alloys thereof, and carbon materials such as carbon cloth and carbon paper. Among these, metallic materials, particularly copper, nickel, or alloys thereof, are preferred.
[0117] Current collector shapes include metal foil, metal cylinder, metal coil, metal plate, and Examples include spand metal, punched metal, and foamed metal. In the case of carbon materials, carbon sheets and carbon Examples include thin films and carbon cylinders. Of these, metal foil is preferred. It may be formed in a mesh-like structure. The thickness of the metal foil is arbitrary, but is usually 1 μm or more, preferably 3 μm or more, more 5 μm or more, usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm It is less than m. If the metal foil is thinner than this range, it may lack the necessary strength to function as a current collector. Yes. Conversely, if the metal foil is thicker than this range, its handling may be impaired.
[0118] The negative electrode can be manufactured by conventional methods. For example, the electrode mixture sheet and the current collector can be bonded together with an adhesive. Methods include stacking the materials and then vacuum drying them.
[0119] The density of the negative electrode mixture sheet is preferably 1.3 g / cm³. 3 More preferably 1.4g / cm 3 More preferably 1.5 g / cm³ 3 The above applies, and preferably 2.0 g / cm 3 More preferably, 1.9 g / cm³ 3 More preferably, 1.8 g / cm³ 3 Below The range is shown below. If this range is exceeded, the penetration of the electrolyte near the interface between the current collector and the active material is impaired. This can lead to a decrease in performance, particularly in charge-discharge characteristics at high current densities, which may result in a failure to obtain high output power. If the voltage falls below a certain level, the conductivity between the active materials decreases, increasing the battery resistance and potentially preventing high output power from being achieved.
[0120] The thickness of the negative electrode is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the current collector is subtracted. The thickness of the composite sheet is preferably 10 μm or more as a minimum for one side of the current collector. More preferably 20 μm or more, and preferably 500 μm or less as an upper limit. Preferably, the particle size is 450 μm or less.
[0121] (The elemental ratio of fluorine to carbon (F / C ratio)) The binder of this disclosure has an elemental ratio of fluorine to carbon (F / C ratio) in the electrode mixture sheet. Preferably, it should be between 0.40 and 3.00, and between 0.50 and 2.50. This is more preferable. Within this range, electrodes with high strength and low electrode resistance can be produced. Can be made This is preferable in that respect. Note that the elemental analysis values were measured using standard, general methods. For example, the F / C ratio is determined using a MICRO CORDER JM10 (manufactured by J Science Lab) and a sump. Helium quantity: 2 mg, combustion furnace: 950°C, reduction furnace: 550°C, helium flow rate: 200 mL / min, acid CHN was measured simultaneously under a flow rate of 15-25 mL / min, and the average value of four measurements was taken. It can be calculated from this. F / C ratio = average F(wt%) / average C(wt%)
[0122] (Secondary battery) The electrodes manufactured by the method for manufacturing electrodes for secondary batteries of this disclosure are positive in various secondary batteries. It can be used as an electrode or a negative electrode. The above secondary battery is a battery that uses a non-aqueous electrolyte. Yes, lithium-ion batteries can be cited as an example.
[0123] (electrolyte) The above non-aqueous electrolyte is obtained by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts. It can be used.
[0124] The organic solvent used for dissolving electrolyte salts is not particularly limited, but propylene carbonate Nate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2- Dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate Known hydrocarbon solvents such as ethyl methyl carbonate; fluoroethylene carbonate A fluorinated solvent such as ionate, fluoroether, or fluorinated carbonate or Two or more types can be used.
[0125] Examples of electrolyte salts include LiClO4, LiAsF6, LiBF4, LiPF6, Examples include LiN(SO2CF3)2 and LiN(SO2C2F5)2, and their cycle characteristics. In particular, LiPF6, LiBF4, LiN(SO2CF3)2, and LiN(SO2CF3)2 are favorable. 2C2F5)2 or a combination thereof is preferred.
[0126] The concentration of the electrolyte salt should be 0.8 mol / liter or higher, and even 1.0 mol / liter or higher. It is necessary. The upper limit depends on the organic solvent used for dissolving the electrolyte salt, but is usually 1.5 mol / liter or less. That is the case.
[0127] (Battery design) The electrode mixture group includes a laminated structure in which the above positive electrode and negative electrode are separated by a separator, and the above In any of the structures in which the positive and negative electrodes are spirally wound around the separator mentioned above good.
[0128] (Separator) The secondary battery of this disclosure preferably further comprises a separator. The material and shape of the above separator should be stable in the electrolyte and have excellent liquid retention properties. Not limited to, publicly known materials may be used. In particular, the electrolyte or the disclosed Made from materials that are stable to the electrolyte used in alkaline metal secondary batteries, such as resin and glass. Materials such as porous sheets or nonwoven fabrics made from fibers, inorganic materials, etc., which have excellent liquid retention properties. It is preferable to use it.
[0129] Examples of materials for resin and glass fiber separators include polyethylene, polypropylene, etc. Polyolefins, aromatic polyamides, PTFE, polyethersulfones, glass film Can be used. Polypropylene / polyethylene 2-layer film, polypropylene These materials, such as 3-layer films of polyethylene / polypropylene, are used individually. You may use two or more types in any combination and ratio. In particular, the above separator has good electrolyte permeability and shutdown effect, Porous sheets or nonwoven fabrics made from polyolefins such as polyethylene and polypropylene. It is preferable that the above apply.
[0130] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, and 8 μm m or more is more preferable, and is usually 50 μm or less, preferably 40 μm or less, and 30 A thickness of μm or less is even more preferable. If the separator is too thin compared to the above range, the insulating properties and mechanical strength will be compromised. This may result in a decrease in performance. Furthermore, if the thickness exceeds the above range, battery performance such as rate characteristics will decrease. Not only can this happen, but the overall energy density of the electrolyte battery may decrease. be.
[0131] Furthermore, when using porous materials such as porous sheets or nonwoven fabrics as separators, The porosity of the material is arbitrary, but is usually 20% or more, preferably 35% or more, and preferably 45% or more. It is even more preferable that it is usually 90% or less, preferably 85% or less, and even more preferable that it is 75% or less. This is preferable. If the porosity is too small compared to the above range, the film resistance will increase and the rate characteristics will be affected. The condition tends to worsen. Furthermore, if the value exceeds the above range, the mechanical strength of the separator decreases. Furthermore, the insulating properties tend to decrease.
[0132] Furthermore, while the average pore size of the separator is arbitrary, it is usually 0.5 μm or less, and 0.2 μm or less. The lower range is preferable, and is usually 0.05 μm or larger. If the average pore size exceeds the above range, Short circuits become more likely. Furthermore, below the above range, the film resistance increases and the rate characteristics deteriorate. It may happen.
[0133] On the other hand, examples of inorganic materials include oxides such as alumina and silicon dioxide, and aluminum nitride. Nitrides such as silicon nitride and sulfates such as barium sulfate and calcium sulfate are used, and particulate matter Materials in a crystalline or fibrous form are used.
[0134] In terms of form, thin films such as nonwoven fabrics, woven fabrics, and microporous films are used. In terms of shape, materials with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm are preferably used. In addition to the independent thin film shapes described above, composites containing the above inorganic particles using a resin binder are also available. A separator can be used in which a porous layer is formed on the surface of the positive electrode and / or negative electrode. For example, alumina particles with a particle size of less than 1 μm for 90% of the positive electrode are placed on both sides, and a fluororesin is used as a binder. One possible method is to form a porous layer.
[0135] (Percentage of electrode combination group) A battery using electrodes manufactured by the method for manufacturing electrodes for secondary batteries of this disclosure is an electrode mixture. The proportion of the group's volume to the battery's internal volume (hereinafter referred to as the electrode mixture group occupancy rate) is typically 40%. The above is the standard, with 50% or more being preferable, and usually 90% or less, with 80% or less being preferable. stomach.
[0136] If the electrode mixture group occupancy rate falls below the above range, the battery capacity may decrease. Also, When the temperature exceeds the specified range, the void space is reduced, and the components expand due to the high temperature of the battery. The vapor pressure of the electrolyte's liquid component increases, causing the internal pressure to rise, which affects the battery's charging and discharging cycle. This can reduce various properties such as return performance and high-temperature storage, and furthermore, it can cause gas to escape from the internal pressure. The valve may activate.
[0137] The current collection structure is not particularly limited, but it is more effective in improving the high current density charge / discharge characteristics by using an electrolyte. To achieve this effectively, it is preferable to use a structure that reduces resistance in the wiring and connection parts. When internal resistance is reduced in this way, the effect of using an electrolyte is particularly pronounced.
[0138] In the case where the electrode mixture group has the above-described layered structure, the metal core portions of each electrode mixture layer are bundled together and welded to the terminal. A structure formed in this way is preferably used. When the area of a single electrode mixture is large, Since the resistance increases, it is also preferable to reduce the resistance by providing multiple terminals within the electrode mixture. Used. In the case of electrode mixtures with the above wound structure, multiple rings are used in the positive and negative electrodes, respectively. By creating a cord structure and bundling the wires at the terminals, the internal resistance can be reduced.
[0139] The material of the outer casing is not particularly limited as long as it is a material that is stable with respect to the electrolyte used. Physically, nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium Metals such as nesium alloys, or laminated films of resin and aluminum foil (laminate film) ) is used. From the perspective of weight reduction, aluminum or aluminum alloy metal, laminate A film is preferably used.
[0140] In exterior cases using metals, laser welding, resistance welding, and ultrasonic welding are used to weld the metals together. A sealing structure is created by welding, or the above metals are used via a resin gasket. One example is a crimped structure. Examples include those that create a sealed and airtight structure by heat-fusing resin layers together. To improve performance, a different resin than the one used in the laminate film is placed between the above resin layers. An intermediary may be used. In particular, when a sealed structure is formed by heat-sealing the resin layer via the current collection terminal. Since this involves bonding metal and resin, the intervening resin should be a resin with polar groups or a resin with polar groups. The introduced modified resin is preferably used.
[0141] The shape of the secondary battery in this disclosure is arbitrary, and for example, cylindrical, prismatic, laminated, or coin-shaped. Examples include large shapes. The shapes and configurations of the positive electrode, negative electrode, and separator are as follows: It can be used by changing the shape of the battery according to the battery type. [Examples]
[0142] The present disclosure will be described in detail below based on examples. In the following examples, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "quality," respectively. This represents "amount in percentage."
[0143] [Example 1] Referencing example 2 of International Publication No. 2015-080291, prepare a PTFE aqueous dispersion (solid). A 31.2% mass PTFE-A sample was obtained. The measured standard specific gravity was 2.16.
[0144] [Example 2] Referencing example 3 of International Publication No. 2015-080291, prepare a PTFE aqueous dispersion (solid A 30.9% mass PTFE-B was obtained. The amount of fluorine-containing surfactant used in the final PTFE The yield was 3290 ppm. The measured standard specific gravity was 2.15.
[0145] [Example 3] Based on example 1 of international publication No. 2012 / 086710, aqueous dispersion of modified PTFE. A PTFE-C molecule was obtained. The polymer concentration of the obtained aqueous dispersion was 30.1% by mass, with an average primary concentration. The particle size was 0.18 μm. The measured standard specific gravity was 2.16.
[0146] [Example 4] Referencing Preparation Example 1 of International No. 2012-063622, an aqueous dispersion of PTFE particles P TFE-D was obtained. The measured standard specific gravity was 2.19.
[0147] Weigh out 0.25 g of Li-100 (acetylene black) as a conductive additive, and use it as a solvent. Add ultrapure water and mix with a mixer at 2000 rpm for 3 minutes to prepare the conductive additive dispersion. Then, 4.75g of aqueous dispersion PTFE-A was added as solid content, and then ultrapure water was added. In addition, the concentration of solids was adjusted. The final amount of solvent was 45g, after which mixed raw materials were used. The mixture was stirred in a tar for 1 hour to prepare it. Then, a spray dryer (manufactured by Tokyo Rikakikai Co., Ltd.) was used. A dried powder was obtained (inlet temperature 140°C, airflow 0.60 m³ / min, flow rate 5.5 g / min). Next, vacuum drying (100°C, 8 hours) was performed to obtain binder 1. As shown in Table 1, the type and amount of PTFE aqueous dispersion, the type and amount of conductive additive, and the amount of solvent were changed, and the binding Agents 2-11 were obtained. The moisture content of binders 1 to 11 was measured, and all were found to be 250 PPM or less.
[0148] [Table 1]
[0149] [Example 5] Dilute the aqueous dispersion PTFE-D obtained in Preparation Example 4 to a solid content concentration of 15% in a container equipped with a stirrer. The PTFE was gently stirred in the presence of nitric acid to solidify. The solidified PTFE was then separated. Remove and dry at 160°C for 18 hours to obtain PTFE-E in powder form without conductive additives. Ta.
[0150] (Example 1) <Preparation of positive electrode mixture sheet> Li(Ni) is used as the positive electrode active material. 0.6 Mn 0.2 Co 0.2 )O2(NMC622) and later While taking into account the amount of conductive additive contained in the binder to be added, weigh Li-100 as the conductive additive. The mixture was measured and stirred in a mixer at 1500 rpm for 10 minutes to obtain the mixture. Container containing the mixture Add the prepared binder 1 and stir in a kneader at 40 rpm for 2 hours to create the mixed powder composition. The composition was determined by mass ratio of positive electrode active material:PTFE:total conductive additive = 95.5:2:2.5. . The resulting mixed powder composition was formed into a bulk form and then rolled into a sheet. Afterward, the rolled sheet obtained earlier is folded in half to coarsely crush it, and then returned to a bulk state. After shaping, it is pressed into a sheet using a metal roller on a hot plate heated to 80 degrees Celsius. The process of rolling to promote fibrillation was repeated four times. After that, it was rolled further. This resulted in obtaining a positive electrode mixture sheet with a thickness of approximately 500 μm. Furthermore, the positive electrode mixture sheet was divided into 5 cm × The material was cut into 5cm pieces and placed into a roll press machine heated to 80 degrees Celsius for rolling. To promote fibrillation, a load of 2kN was repeatedly applied to adjust the thickness. The mixture was adjusted so that the final cathode composite layer thickness was 90 μm and the density was 3.20 g / cc. The mixture was adjusted to obtain a positive electrode mixture sheet.
[0151] Each test was conducted using the following method. [Intensity Measurement] Tensile testing machine (Shimadzu Corporation Autograph AGS-X series AGS-100NX) Measurements were taken using a 4mm wide strip-shaped positive electrode mixture sheet test piece under conditions of 100mm / min. The distance between chucks was set to 30 mm. Displacement was applied until fracture occurred, and the best result was measured. The maximum stress was used as the strength for each sample. Comparative Example 1 was set to 100 for comparison.
[0152] [Electrode resistance measurement] Cut the positive electrode mixture sheet into a 5.0 cm wide x 10 cm long square to make a test specimen. Resistivity Using a Loresta GP (manufactured by Mitsubishi Chemical Corporation), the four-terminal resistance of the positive electrode active material layer was measured according to JIS K71. Measurements were taken according to 94;1994. A lower resistance value indicates better battery characteristics. A: Less than 20 Ωcm B: Less than 20-50 Ωcm C: Less than 50-100 Ωcm D: Less than 100-200 Ωcm E: 200 and above
[0153] (Examples 2 and 3) A positive electrode mixture sheet was obtained in the same manner as in Example 1, except that the binder having the composition shown in Table 1 was used.
[0154] (Examples 4 to 7) The conductive aid mixed with NMC was changed to Super-P Li (furnace black). A positive electrode mixture sheet was obtained in the same manner as in Example 1, except that the binder having the composition shown in Table 1 was used. obtained. (Example 11) The conductive aid mixed with NMC was changed to carbon ECP (Ketjen black). A positive electrode mixture sheet was obtained in the same manner as in Example 1, except that the binder having the composition shown in Table 1 was used. <00�1320>[[ID=2०]]<0001з21>(Examples 8, 9) As the positive electrode active material, Li(Ni 0.8 Mn 0.1 Co [[ID=2८]] 0.1 )O2 (NMC811) and Li-100 as the conductive aid and binder ८ were used. The mixed powder composition was positive electrode active material:P TFE:FT7000 (multilayer carbon nanotube with an average diameter of 7 to 11 nm and a length of 5 to 20 μm):Li-100 = 95.5:2:0.04:2.46 by mass ratio. Otherwise, a positive electrode mixture sheet was obtained in the same manner as in Example 1. Example 9 was also conducted in the same manner. TFE:FT7000 (multilayer carbon nanotube with an average diameter of 7 to 11 nm and a length of 5 to 20 μm):Li-100 = з5.5:2:0.04:2.46 by mass ratio. Otherwise, a positive electrode mixture sheet was obtained in the same manner as in Example 1. Example 9 was also conducted in the same manner. ube):Li-100 = 95.5:2:0.04:2.46. Otherwise, a positive electrode mixture sheet was obtained in the same manner as in Example 1. A positive electrode mixture sheet was obtained in the same manner as in Example 1. Example 9 was also conducted in the same manner.
[0156] (Example 10) As the positive electrode active material, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2 (NMC811) and Li-100 as the conductive aid and binder 10 were used. The mixed powder composition was positive electrode active material: PTFE:FT7000:Li-100 = 95.5:2:0.11:2.34 by mass ratio.Otherwise, a positive electrode mixture sheet was obtained in the same manner as in Example 1. PTFE:FT7000:Li-100 = 95.5:2:0.11:2.34 by mass ratio. Otherwise, a positive electrode mixture sheet was obtained in the same manner as in Example 1. A positive electrode mixture sheet was obtained in the same manner as in Example 1.
[0157] <Fabrication of Positive Electrode> The positive electrode mixture sheet was bonded to a 20 μm aluminum foil. N-methylpyrrolidone was used as the adhesive. Polyvinydenine fluoride (PVDF) is dissolved in NMP, and carbon nanotubes ( A slurry containing dispersed CNTs was used. The above-mentioned adhesive was applied to aluminum foil to prepare the sample. Place the sheet-shaped cathode mixture on top, ensuring no air bubbles are trapped, and vacuum dry at 120°C for 30 minutes. A positive electrode sheet integrated with the current collector was manufactured.
[0158] <Preparation of electrolyte solution> As organic solvents, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) ) weigh out a mixed solvent (EC:EMC = 30:70 (volume ratio)) into a sample bottle, and add it to this Fluoroethylene carbonate (FEC) and vinylene carbonate (VC) are mixed at 1% by mass. The concentration of LiPF6 salt in the electrolyte solution prepared by dissolving the salts is set to 1.0 mol / L. The electrolyte was obtained by mixing at 23°C.
[0159] <Battery manufacturing> Using the positive electrode sheet and polyethylene separator prepared above, and Li metal as the negative electrode, I manufactured a coin cell battery. More specifically, in a dry room, a separator was placed between the positive and negative electrodes. They were sandwiched together to form an electrode body battery. This electrode body battery was then placed in a battery case made of stainless steel. It was housed in a CR2032 type coin cell battery component. Electrolyte was injected into the battery case. The case was sealed using a crimping machine to obtain the non-aqueous electrolyte lithium-ion secondary battery of the example.
[0160] [Initial discharge capacity test] The lithium-ion secondary battery manufactured as described above is subjected to a current equivalent to 0.5C at 25°C. Constant current-constant voltage charging up to 4.3V (hereinafter referred to as CC / CV charging) (0.1C cutoff) After that, discharge to 3V with a constant current of 0.5C, and repeat this for 3 cycles. The initial discharge capacity was determined from the discharge capacity of the eye. The initial capacity of the reference example was set to 100 for comparison.
[0161] (Comparative Example 1) Except for using powdered PTFE-E without conductive additives, the non-aqueous electrolyte was the same as in Example 1. A lithium-ion secondary battery was obtained.
[0162] (Comparative Example 2) Using powdered PTFE-E without conductive additives, the conductive additive is changed to Super-P Li. A non-aqueous electrolyte lithium-ion secondary battery was obtained in the same manner as in Example 1, except that it was modified.
[0163] (Reference example) We weighed NMC811 as the positive electrode active material and Li-100 and FT7000 as conductive additives. The mixture was then stirred in a mixer at 1500 rpm for 10 minutes to obtain the mixture. The prepared powdered PTFE-E is added and stirred in a kneader at 40 rpm for 2 hours to form a mixed powder. A composition was obtained. The composition, by mass ratio, was positive electrode active material:PTFE:FT7000:Li-100=9 The ratio was set to 5.5:2:0.04:2.46. An electrode mixture sheet was prepared using the same procedure as in Example 8. A non-aqueous electrolyte lithium-ion secondary battery was obtained.
[0164] (Comparative Example 3) Li(Ni) is used as the positive electrode active material. 0.8 Mn 0.1 Co 0.1 )O2(NMC811), conductive Weigh out Li-100 as an additive and mix it in a mixer at 2000 rpm for 10 minutes to form a mixture. The mixture was obtained. The prepared aqueous dispersion PTFE-D was added to the container containing the mixture and mixed in a kneader for 4 minutes. The mixture was stirred at 0 rpm for 2 hours to obtain a mixed powder composition. The composition was by mass ratio of positive electrode active material:PTFE. The conductive additive ratio was set to 95.5:2:2.5. Aggregates were observed in the dispersion before drying. Therefore, instead of spray drying, it was dried on a hot plate at 110°C for 1 hour. Vacuum drying (100°C, 8 hours) was performed to obtain the mixed powder composition. Electrical processing was carried out in the same procedure as in Example 8. An electrode mixture sheet was prepared, and a non-aqueous electrolyte lithium-ion secondary battery was obtained.
[0165] [Table 2]
[0166] [Table 3]
[0167] The fibril diameters of Examples 1 and 3 were measured, and the median fibril diameters were 40 and 3, respectively. It was 1 nm. The fibril diameters of Examples 4 and 5 were measured, and the median fibril diameters were 33 and 4, respectively. It was 3nm. The fibril diameters of Examples 9, 10, and 11 were measured, and the median fibril diameters were as follows: The wavelengths were 51, 67, and 40 nm.
[0168] Comparative Example 1 and Examples 1-3 show that electrodes with high tensile strength and low resistance can be fabricated. ru. Furthermore, a suitable range for conductive material and PTFE was found from Comparative Example 2 and Examples 4-7. Also, Comparative Example 3 From Example 8, by using a binder that is a powder that does not contain electrode active material, the battery characteristics We found ways to improve. [Industrial applicability]
[0169] The method for manufacturing electrodes for secondary batteries using a non-aqueous electrolyte disclosed herein applies to lithium-ion secondary batteries, etc. It can be used in the manufacture of electrodes used in batteries.
Claims
1. The powder is made of a composition essentially containing a polytetrafluoroethylene resin and a conductive assistant, and does not contain an electrode active material. A binder for a secondary battery using a non-aqueous electrolyte, characterized in that the binder is in the form of particles granulated by spray drying.
2. 2. The binder for a secondary battery using a non-aqueous electrolyte according to claim 1, wherein the elemental ratio of fluorine to carbon (F / C ratio) measured by elemental analysis is 0.4 or more and 3.0 or less.
3. A binder for a secondary battery using the nonaqueous electrolyte according to claim 1 or 2, which contains polytetrafluoroethylene resin and a conductive assistant in a weight ratio of 90:10 to 65:
35.
4. A method for producing the binder for a solid secondary battery according to claim 1 or 2, comprising the steps of: A method for producing a binder for a secondary battery using a non-aqueous electrolyte, the method comprising: a step (A) of mixing PTFE and a conductive assistant in the presence of a liquid medium; and a step (B) of drying the composition obtained by the step (A) by spray drying.
